Retrospective Evaluation of Different Shade Selection Methods in the Context of the Vital Bleaching Technique - TÜRKMEN, CAFER; KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: This retrospective study was performed to evaluate the correspondence between digital image analysis and spectrophotometry tooth shade results. Methods: The study population consisted of 10 patients. Office bleaching was performed using an in-office whitening. Tooth shade was analysed by spectrophotometry and image analysis of digital photographs at baseline, and at 1-week and 3-month follow-up visits. The correspondence between the two methods was evaluated based on the total color change (Delta E), calculated using lightness, chroma, and hue (LCH) values for spectrophotometry and lightness, red-green, blue-yellow (LAB) values for digital image analysis. The Mann-Whitney U, Wilcoxon signed rank and Kruskal-Wallis tests were used for the statistical analyses (p<0.05). The correspondence between digital image analysis and spectrophotometry results was determined using the intraclass correlation coefficient (ICC). Results: At the 3-month follow-up, there were no significant differences in tooth shade results between the spectrophotometry and digital image analysis methods (p=0.855), which showed strong agreement (ICC=0.983). Conclusion: Digital image analysis may be a useful alternative to spectrophotometry for tooth shade selection.
Keywords: Bleaching; Digital image analysis; Shade Selection; Spectrophotometer; COLOR; PROTOCOLS; HOME